2022
DOI: 10.1371/journal.pgen.1010496
|View full text |Cite
|
Sign up to set email alerts
|

wnt16 regulates spine and muscle morphogenesis through parallel signals from notochord and dermomyotome

Abstract: Bone and muscle are coupled through developmental, mechanical, paracrine, and autocrine signals. Genetic variants at the CPED1-WNT16 locus are dually associated with bone- and muscle-related traits. While Wnt16 is necessary for bone mass and strength, this fails to explain pleiotropy at this locus. Here, we show wnt16 is required for spine and muscle morphogenesis in zebrafish. In embryos, wnt16 is expressed in dermomyotome and developing notochord, and contributes to larval myotome morphology and notochord el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 91 publications
1
20
0
Order By: Relevance
“…Additionally, recent evidence from crispant zebrafish models support the potential for wnt16 to exert pleiotropic effects on bone and lean muscle mass through a function in myogenic precursors. (Watson et al, 2022). With the exception of the occipital region, all other areas of the skull that vary between wnt16 crispants and controls are associated with the expansion of the oral cavity required for suction feeding in fishes (Day et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, recent evidence from crispant zebrafish models support the potential for wnt16 to exert pleiotropic effects on bone and lean muscle mass through a function in myogenic precursors. (Watson et al, 2022). With the exception of the occipital region, all other areas of the skull that vary between wnt16 crispants and controls are associated with the expansion of the oral cavity required for suction feeding in fishes (Day et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…We also included germline mutant lines for sost (7 mutants; 9 heterozygotes; 8 control fish) and wnt16 (5 mutants; 6 heterozygotes; 3 control fish). Generation of crispants for plod2 and wnt16 was previously described (Watson et al, 2020; 2022); Generation of crispants for meox1 was performed using the methods described in Watson et al, 2020. In this case, Cas9:gRNAs targeting two distinct regions (gRNA1: GTCAGGAGTCCTCATTCGGG; gRNA2: GGTTGACTGCGATCTCGTAG) were injected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spatiotemporal expression of Wnt16 has been described by several studies: during embryonic development, Wnt16 is selectively expressed in mouse perichondrium, periosteum and joints, and in zebrafish dermomyotome and developing notochord ( 105 , 106 ), while in postnatal environment, Wnt16 is highly expressed in mouse cortical bone and zebrafish notochord sheath ( 56 , 105 ). Researches have suggested that changes in hormone level caused by aging, diseases and hormone therapy can affect the expression of Wnt16.…”
Section: Discussionmentioning
confidence: 99%